THE EFFECT OF ECOENZYME SPRAYING ON PLANT HEIGHT AND LEAF AREA OF PAKCOY (Brassica rapa L.) CULTIVATED HYDROPONICALLY - Novita Sukawati; Resti Fevria; Vauzia; Siska Farma (Jurnal Serambi Biologi, 2022)
In the hydroponic system, AB Mix nutrition is one of the standard nutrients used. In addition to the use of AB Mix, the use of ecoenzymes in hydroponic plants is also a big concern. This is what makes the authors interested in using ecoenzyme to help AB Mix for hydroponic growth and maintenance of pakcoy (Brassica rapa L.). This study aims to determine the effect of spraying ecoenzyme on the growth of pakcoy (Brassica rapa L.) which is cultivated hydroponically. This research will be carried out from December 2021 to February 2022 at the Plant Physiology Laboratory and the wire house of the Biology Department, FMIPA UNP. This study used a completely randomized design (CRD) with 5 treatments and 5 replications. Consists of: P1 (Control), P2 (1mL ecoenzyme + 1 L water), P3 (2mL ecoenzyme + 1 L water), P4 (3mL ecoenzyme + 1 L water), P5 (4mL ecoenzyme + 1 L water). The data obtained were analyzed by means of variance (ANOVA) with DMRT further test. The results of the study of spraying ecoenzyme on pakcoy (Brassica rapa L.) which were cultivated hydroponically had an effect on plant height growth with the highest average of 14.4 cm, and had no effect on leaf area.